Corneal cell viability and structure after transcorneal freezing–thawing in the human cornea - Joo Youn Oh (Dove Medical Press, 2010)
Joo Youn Oh1,2, Hyun Ju Lee1,2, Sang In Khwarg1,2, Won Ryang Wee1,21Department of Ophthalmology, Seoul National University College of Medicine, Seoul, Korea; 2Seoul Artificial Eye Center, Seoul National University Hospital Clinical Research Institute, Seoul, KoreaPurpose: Although cryotherapy has long been used to eradicate corneal lesions, there have been no reports of adverse effects of cryotherapy on human corneas. We performed this study to evaluate and characterize ultrastructural damage to the human cornea following the transcorneal freezing-and-thawing procedure.Methods: Seven human donor corneas were randomly divided into three groups. 1, 2, and 3 repetitive freezing-and-thawing procedures were respectively applied to donor corneas in each group. A cryoprobe was cooled to -80°C, and placed on the anterior surface 1.5 mm central to the limbus for 3 seconds. Samples were then allowed to spontaneously defrost. A cornea without the treatment was used as a control. Samples were evaluated through hematoxylin & eosin staining, TUNEL assay, and electron microscopy.Results: After transcorneal cryoinjury, it was observed that corneal endothelial cells were lost and Descemet’s membrane was denuded where the cryoprobe was applied. Corneal stromal cells were damaged, and the damage was more marked in the posterior stroma. The extent of damage increased with an increasing number of freezing–thawing repetitions. In contrast, corneal epithelial cells showed no cryo-induced damage, and Bowman’s layer remained intact in all groups.Conclusions: The susceptibility to transcorneal cryo-injury differed among the corneal layers; the corneal endothelium was most susceptible, and the epithelium was least susceptible. Caution would thus be advised in regard to the potential damage in corneal endothelium when treating patients with corneal lesions using transcorneal cryotherapy.Keywords: apoptosis, cryotherapy, endothelium, keratocyte